Determination of Comfortable Safe Width in an Exclusive Motorcycle Lane - Law, Teik Hua; Radin Sohadi, Radin Umar (2005)

(untitled)
Abstract: motorcyclists contributed almost 60% of the fatal accidents in Malaysian. An effective engineering approach to this problem is by segregating these vulnerable road users from other motorized traffic through the provision of an exclusive motorcycle lane. At present there are no specific standards that are available to assess design criteria of exclusive motorcycle lanes in Malaysia. However, it is important to specify standards for exclusive motorcycle lanes as the optimum control width should be comfortable for all riders. The estimation of safe control motorcycle lane width was based on a logistic regression of binary response. The dependent variable is assumed to be either comfortable overtaking or non-comfortable overtaking or non-comfortable overtaking. The resulting analysis was used to suggest a safe control width of pavement for a straight section of an exclusive motorcycle lane. Result indicates that the safe control width of an exclusive motorcycle lane should be 3.81 meters.